MARKETING ANALYZE OF JERUK SIAM (CITRUS NOBILUS LOURVAR) IN DESA PULAU JAMBU KECAMATAN KUOK KABUPATEN KAMPAR - Gita Dewanti; Ermi Tety; Suardi Tarumun (Universitas Lancang Kuning, 2015)
ABSTRACT The marketing of Jeruk Siam principally is about the distribution of the fruits from the farmers to the consumers. This research aims ti analyze: the marketing function, marketing channels, cost, margin, profit, marketing efficiency, and the problem that faced by the marketing institution of Jeruk Siam in Desa Pulau Jambu Kecamatan Kuok Kabupaten Kampar. This research uses the survey method and taking sample of the farmers by the census with the criteria, has minimal 1 hectare of firm land and the age of the plant is about 3-4 years. The sample determining of the marketing institution uses the snow ball sampling method by following the marketing channels. In this reseacrh there are three channels. Channel 1 is the distribution from the farmer to Swalayan Jumbo Mart (super grade, grade A, grade B), channel 2 is the distribution from the farmers-collector-retailer (grade B, grade C, usual grade), channel 3 is the distribution from the farmers to the retailres. The marketing function those are influence to the farmers are exchange function and marketing facility function. The result of the research shows the efficient channel. Seen from the efficiency, channel 3 has 0,93%. Profit, channel 2 grade C has Rp. 1.290,21/kg. Marketing cost, channel 3 has Rp. 93,344/kg. Margin, channel 1 Super grade has Rp. 1.750/kg, and the farmer’s share, channel 3 has 95,19%. The problem of the farmers are the extreme weather, there is no irigation, anda plant disease, while the problems of the marketing institution is the endurance of the fruits for distributing to the far place.